Influence of Organizational Innovation on the Performance of Coffee Cooperatives in Kenya - Kuguru, Peter Ngibuini; Jaensson, Jan-Erik Jaensson; Nganga, Kinyanjui Nganga (Journal of Business and Strategic Management, 2022)
Purpose: The purpose of the study was to assess the influence of organizational innovation on the performance of coffee cooperatives in Kenya. Methodology: A descriptive research design was applied. The target population of this study was 525 coffee cooperative societies in Kenya registered with the Commissioner for Cooperatives and licensed by AFFA (Coffee Directorate) as at 30th of October 2016. The sample size was 227 respondents. Structured questionnaires were used to collect primary data from the selected respondents. Findings: The results revealed that organizational innovation and performance are positively and significantly related (Î²=0.75, p=0.007). Unique Contributions to Theory, policy and practice: The study recommended firms to adopt new technologies for cultivation of organizational innovations. They need to be proactive in their research and development departments by incorporating technological advancements in order to maximize the potential that is in innovation strategies. Restructuring of the internal organization is necessary given a firm that requires efficiency and effective processes for better performance. The results of this study will contribute new knowledge which will provide the government and other stakeholders with better ways of managing co-operatives and improving their production.